Malignant Glandular Triton Tumor Arising in the Radial Nerve with Prolonged Survival: A Case Report and Review of the Literature - Batool M. AlAli; Samir S. Amr (Hindawi Limited, 2021)
Divergent differentiation is a well-known phenomenon in malignant peripheral nerve sheath tumors (MPNST) which occurs approximately in 15% of these tumors, usually towards mesenchymal elements. Differentiation towards epithelial components, however, is quite uncommon, and even exceptionally rare is concomitant mesenchymal and glandular differentiation. To our knowledge, only 14 cases of MPNST with both mesenchymal (rhabdomyoblastic) and glandular differentiation had been reported, and only two of these tumors had frankly malignant glandular components. Herein, we report the third such case. A 26-year-old male, without any of the stigmata of NF1, presented with a 2-year history of pain in his left shoulder and an elbow swelling of six-month duration. The tumor was initially diagnosed clinically as a neurofibroma at a local hospital. The patient underwent excision of the mass there, and pathological examination at that hospital showed the tumor to be MPNST. Six months later, the patient was referred to our hospital, a tertiary care medical center, with recurrent swelling at the same location. Histopathological material from the referral hospital was reviewed, and the tumor was diagnosed as MPNST with rhabdomyoblastic differentiation or malignant triton tumor (MTT) that contained in addition foci of malignant glandular epithelium. The patient refused any surgical intervention. He received three cycles of chemotherapy followed by radiotherapy with excellent response and marked reduction in the size of the tumor. The patient had prolonged survival for 10 years following the initial resection of the tumor.